Radiographic aspects of acute community-acquired bacterial pneumonia and pulmonary tuberculosis in children - Rakotomalala, Rivo Lova Herilanto; Rakotondravelo, Harimino Mireille; Ranivoson, Andrianina Harivelo; Robinson, Annick Lalaina (International Journal of Research in Medical Sciences, 2021)
Background: The etiological diagnosis of pneumonia is often difficult because of the impossibility of microbiological confirmation most of the time. Therefore, chest X-ray is still essential for a positive diagnosis and etiological orientation. The main objective of our study was to describe the radiographic aspects of acute community-acquired pneumonia and tubercular pneumonia in children. Methods: This was a descriptive retrospective study conducted at the university hospital mother and child of Tsaralalana from January 1st to July 31st, 2017. Results: Sixty-nine cases of pneumonia were included, including 13 cases of TB pneumonia and 46 cases of acute community-acquired pneumonia. The average age was 36.68 months with a male predominance. Clinically, respiratory functional signs predominated in both cases. Alteration in general condition was mainly observed in tubercular pneumonia (26.08%). Alveolar syndromes were present in 43.47% of TB pneumonias and 36.94% of acute community-acquired pneumonia. With regard to the radiographic images, alveolar involvement was common to both types of pneumonia; the nodular image was present in 8.69% of the tubercular pneumonias and 2.17% of the acute community-acquired pneumonia; the cavity image was present only in the tubercular pneumonia (p=0.04); the right-sided location predominated in both cases. Conclusions: X-ray images were common to both TB pneumonia and acute community-acquired pneumonia; some images were specific to TB pneumonia. However, the etiologic orientation of pneumonia is based on a combination of epidemiologic, clinical, and radiographic evidence.